A Printing‐Centric Approach to the Electrostatic Modification of Polymer/Clay Composites for Use in 3D Direct‐Ink Writing. Issue 8 (12th February 2018) - Rauzan, Brittany M.; Lehman, Sean E.; McCracken, Joselle M.; Lee, Jonghun; Lin, Xiao‐Min; Sandy, Alec; Narayanan, Suresh; Rogers, Simon A.; Nuzzo, Ralph G.
Abstract: Polymer/clay composite inks are exceptionally useful materials for fabrication processes based on 3D direct‐ink writing, however, there remains an insufficient understanding of how their physiochemical dynamics impact printability. Using a model system, N ‐isopropylacrylamide/Laponite, the electrostatic interactions between Laponite platelets are modified to tune critical rheological properties in order to improve printability. Rheological measurements and X‐ray scattering experiments are carried out to monitor the nano/micro‐structural dynamics and complex physicochemical interactions of Laponite as it impacts complex modulus in the linear region, flow behavior, thixotropy, and yield stress of the composite ink. Modification of the electrostatic interactions between platelets reduces the yield stress of the material, while maintaining a complex microstructure that allows for sufficient recovery times upon removal of stress to form stable, and thus printable, filaments. A printing‐centric approach is established based on a fundamental understanding of electrostatic inter‐particle interactions, harnessing the innate microstructure of Laponite in 3D direct‐ink writing of composites. Abstract : At the crux of direct‐ink writing are yield‐stress fluids, such as polymer/clay composite inks. There is, however, a lack of understanding how the physiochemical dynamics of the polymer/clay composite impacts the printability of these inks. Here, a printing‐centric model based on the modification of the electrostatic interactions that mediate the microstructure of particle associations in polymer/clay composite inks is presented.